2020
DOI: 10.31234/osf.io/6vgf4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlates of Health-Protective Behavior During the Initial Days of the COVID-19 Outbreak in Norway

Abstract: The coronavirus outbreak manifested in Norway in March 2020. It was met with a combination of mandatory changes (closing of public institutions) and recommended changes (hygiene behavior, physical distancing). It has been emphasized that health-protective behavior such as increased hygiene or physical distancing are able to slow the spread of infections and flatten the curve. Drawing on previous health-psychological studies during the outbreak of various pandemics, we investigated psychological and demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 28 publications
5
37
1
3
Order By: Relevance
“…As knowledge and media exposure were, on average, quite high. It is similar to a result of the study conducted in Norway, Northern Europe which showed that knowledge had no or even a negative relationship with engagement in protective behaviour [18]. There are fluctuations in the level of preventive behaviours from COVID-19 at different time sequences where they were higher when assessed through the first interview, then decreased through the second interview and re-increased through the third one.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As knowledge and media exposure were, on average, quite high. It is similar to a result of the study conducted in Norway, Northern Europe which showed that knowledge had no or even a negative relationship with engagement in protective behaviour [18]. There are fluctuations in the level of preventive behaviours from COVID-19 at different time sequences where they were higher when assessed through the first interview, then decreased through the second interview and re-increased through the third one.…”
Section: Discussionsupporting
confidence: 85%
“…Also, an Australian study conducted in an earlier stage of the pandemic by Faasse and Newby [17] found positive predictions by media exposure, concern and worry, as well as effectiveness of behaviour. In addition, confidence in authorities and believing that too much fuss was made resulted in less health-protective behaviour [18]. The participants' knowledge about COVID-19 was poor at the beginning of the pandemic then increased after 4 weeks.…”
Section: Discussionmentioning
confidence: 93%
“…Generelt er sosioøkonomisk status og tilhørende ulikhet i helserelatert livsstil sterke prediktorer for sykelighet (11). Kvinner følger oftere helserelaterte råd enn menn (11), og norske data indikerer at kvinner tar flere forholdsregler mot å bli smittet (6). Videre synes de landene som rammes hardest av covid-19-pandemien, å vaere kjennetegnet av lav tillit mellom mennesker og til myndighetene (12).…”
Section: Fortolkningunclassified
“…I tråd med tidligere forskning rapporterte jenter å følge smittevernreglene mer enn gutter (4,6). Rapportert oppslutning om reglene var lavest blant de yngste ungdommene.…”
Section: Overholdt Smittevernreglene I Stor Grad Eller Alltid Antallunclassified
See 1 more Smart Citation